The first urban Christians : the social world of the Apostle Paul - Meeks, Wayne A. (New Haven. Yale University., 1983)
Meeks analyzes the letters of Paul to see what kind of people joined the Christian groups in the urban centers and what it was like to be a Christian then.
The urban environment of Pauline Christianity -- The social level of Pauline Christians -- The formation of the ekklesia -- Governance -- Ritual -- Patterns of belief and patterns of life.
Includes bibliographical references (pages 243-278) and indexes.
Keywords: Paul, -- the Apostle, Saint; Christian sociology -- History -- Early church, ca. 30-600.; Christianity, to ca 65 - Sociological perspectives; History